Assessment of the River Water Pollution Levels in Kuantan, Malaysia, Using Ion-Exclusion Chromatographic Data, Water Quality Indices, and Land Usage Patterns - Kozaki, Daisuke; Mohd Hasbi, Ab. Rahim; Wan Faizal, Wan Ishak; M. M., Yusoff; Mori, Masanobu; Nakatani, Nobutake; Tanaka, Kazuhiko (Libertas Academica Ltd, 2016)
Water qualities of three suburban rivers, namely, Kuantan, Belat, and Galing rivers, in Kuantan, Malaysia, were examined effectively by using ion-exclusion/cation-exchange chromatography with water quality indices and land usage data. Specifically, we have focused on evaluating and grasping the effect of sewage/household wastewater discharged from housing areas in the Kuantan district on the river water quality. Based on this study, the following beneficial information were obtained effectively: (1) the pollution levels in the three rivers (Kuantan River: Classes I–III, Belat River: Classes I–III, and Galing River: Classes I–V) are linked with the urbanization level of the river basin area; (2) differences in the biological reactions in the different pollution level rivers are understood; (3) Galing River is among the most polluted rivers not only in Kuantan but also in the Peninsular Malaysia, owing to poor water treatment of the sewage/household wastewater discharged from the river basin area.